Interest Deductions in a Multijurisdictional World - Mihir A. Desai; Dhammika Dharmapala (Center for Economic Studies and ifo Institute (CESifo), 2015)
This paper proposes and evaluates alternative methods for addressing the tax treatment of interest expenses in a multijurisdictional setting. The differential deductibility of debt entailed by various current tax law provisions leads to potential distortions in the patterns of asset ownership across MNCs and various proposed solutions have significant limitations. We suggest alternative regimes – a worldwide debt cap (WDC) and a net financing deduction (NFD) – to address the ownership distortions that we highlight along with other well-established problems of income-shifting through debt. These alternative regimes are extensions to a multinational setting of two general approaches to the neutral treatment of interest expenses - the CBIT (comprehensive business income tax) and ACC (allowance for corporate capital). While these regimes provide solutions to ownership distortions and to problems of “base erosion and profit shifting,” they have the potential disadvantage of restricting other policy parameters.
Keywords: H25; H87; G32; 330; interest deductions; international taxation; base erosion and profit shifting